2012
DOI: 10.1017/s1751731112000857
|View full text |Cite
|
Sign up to set email alerts
|

Effect of disodium fumarate on microbial abundance, ruminal fermentation and methane emission in goats under different forage : concentrate ratios

Abstract: This study investigated the effects of disodium fumarate (DF) on methane emission, ruminal fermentation and microbial abundance in goats under different forage (F) : concentrate (C) ratios and fed according to maintenance requirements. Four ruminally fistulated, castrated male goats were used in a 4 × 4 Latin square design with a 2 × 2 factorial arrangement of treatments and the main factors being the F : C ratios (41 : 59 or 58 : 42) and DF supplementation (0 or 10 g/day). DF reduced methane productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 27 publications
(37 reference statements)
8
29
1
Order By: Relevance
“…Structural carbohydrate-rich diet causes greater production of enteric CH 4 than non-fiber carbohydrate-rich diet in dairy cows [4] because the diet containing large amounts of non-fiber carbohydrates derives propionate production in the rumen, thereby inhibiting rumen methanogen growth [30]. However, some studies for goats showed that the dietary F:C ratio did not affect CH 4 (g/d) emission [10,31]. According to the morphophysiological classification of Hofmann [32], goats and Sika deer were intermediate type and concentrate eaters, respectively, whereas cattle and sheep were grass/roughage eaters.…”
Section: Resultsmentioning
confidence: 99%
“…Structural carbohydrate-rich diet causes greater production of enteric CH 4 than non-fiber carbohydrate-rich diet in dairy cows [4] because the diet containing large amounts of non-fiber carbohydrates derives propionate production in the rumen, thereby inhibiting rumen methanogen growth [30]. However, some studies for goats showed that the dietary F:C ratio did not affect CH 4 (g/d) emission [10,31]. According to the morphophysiological classification of Hofmann [32], goats and Sika deer were intermediate type and concentrate eaters, respectively, whereas cattle and sheep were grass/roughage eaters.…”
Section: Resultsmentioning
confidence: 99%
“…After gas measurement at each time point, 30 μL of gas sample was drawn out immediately from each bottle using a gastight syringe to determine methane concentrations using gas chromatography (GC-2014, Shimadzu, Japan) (Yang et al, 2012). At the end of the 24 h of incubation, the pH value of each in vitro culture was measured immediately using a portable pH-meter (Ecoscan pH 5, Eutech Instruments, Singapore).…”
Section: Methodsmentioning
confidence: 99%
“…Real-time quantitative PCR was performed using the ABI 7300 real-time PCR system (Applied Biosystems, Foster, California, USA). Reaction mixture, amplification conditions and performing progresses were conducted by the method of Yang et al (2012).…”
Section: Methodsmentioning
confidence: 99%